*This preview shows
page 1. Sign up
to
view the full content.*

**Unformatted text preview: **b) Reflect the graph through the y-axis. y = 3-x The positive x-axis is the horizontal asymptote. The y-intercept is (0, 1). c) Shift the graph up 3 units and translate the graph 4 units to the left. y = 3 + 3 x+4 . The line y = 3 is the horizontal asymptote. The y-intercept is (0, 84). d) Reflect the graph over the x-axis, then shift it 2 units to the right. 2 3 = x y The negative x-axis is the horizontal asymptote. The y-intercept is (0, -) 9 1...

View
Full
Document